The Use Level of Chrome Tannage For Rabbit Fur Leather Observed on Tearing Strength, Stitch Tearing Strength, Water Absorption and Organoleptic - Mustakim Mustakim; Imam Thohari; Ipik Agustriyani Rosyida (Jurnal Ilmu dan Teknologi Hasil Ternak (JITEK), 2007)
The purpose of this study was to find out the appropiate of chrome tannage level for rabbit fur leather quality. The result were expected to contribute information for many people who relate with tanning technology, especialy about the use level of chrome tannage for fur leather quality and could as patern to hold further research.The material that used were 12 pieces of three months of rabbit skin. The method is Completely Randomized Design, consist of three treatments of chrome tannage (Chromosal B), they were : B1 (Chromosal B 6%), B2 (Chromosal B 8%), and B3 (Chromosal B 10%). Each of treatment hold on four replications. The variables which measured are tearing strength, stitch teraing strength, water absorption and organoleptic consist of â€œkekuatan buluâ€â€™ â€œkerataan buluâ€ and â€œkelemasan kulitâ€ in fur leather. Data was analysed by analysis variance followed by Duncanâ€™s Multiple Range Test. The result of this research show that the use level of chromosal B give very significant influence among tearing strength, stitch tearing strength and water absorption. It gave significant influence among the organoleptic test. Based on the result, can be concluded that 10 percent of chrome tannage (chromosal B), produce the best result on tearing strength, stitch tearing strength, water absorption and organoleptic for â€œkekuatan buluâ€ and â€œkerataan buluâ€. The incrase of chrome tannage offer will decrease the â€œkelemasan kulitâ€ in fur leather and the best â€œkelemasan kulitâ€ produced by the lowest chrome tannage offer, that was 6 percent of Chromosal B. The best quality of rabbit fur leather produced by 10 percent of chrome tannage offer. Â  Keywords: chrome, tannage, fur leather